Methods of overcoming dormancy in seeds and initial development of Black Wattle - Alberti, Ricardo; Novello, Fernanda Lais; Albarello, Eduardo Alexandre; Torres, Ewerton Jose de Medeiros; Moreira Junior, Fernando de Jesus (Ciência e Natura, 2020)
The objective of this work was to analyze the efficacy of different methods of dormancy break in seeds of Acacia mearnsii De Wild. The work was performed at the UFSM Botany Lab and Forest Nursery, in Frederico Westphalen, RS. The treatments were: (T1) control; (T2) immersion in hot water (90 °C) for 5 minutes, followed by rest; (T3) immersion in hot water (90 °C) for 10 minutes, followed by rest; (T4) chemical scarification with concentrated sulfuric acid for 3 minutes, followed by washing under running water; (T5) chiseling with concentrated sulfuric acid for 5 minutes, followed by washing under running water. The seeds were sown in plastic trays with Oxisol and vermiculite. The results were submitted to analysis of variance and data were differentiated by Test t with 5% of probability. The most efficient treatment to overcome dormancy was T2, presenting 81.29% of germinated seeds and IVG of 18.23 days for germination. This treatment was also the best for the variables of physical vigor and best performing root length and aerial part, and did not differ from improved treatments for diameter and green mass weight.